Epidural Electrotherapy for Epilepsy. Issue 30 (27th June 2018) - Park, Sung‐Won; Kim, Jejung; Kang, Minpyo; Lee, Wonho; Park, Byong Seo; Kim, Hansung; Choi, Se‐Young; Yang, Sungchil; Ahn, Jong‐Hyun; Yang, Sunggu
Abstract: Penetrating electronics have been used for treating epilepsy, yet their therapeutic effects are debated largely due to the lack of a large‐scale, real‐time, and safe recording/stimulation. Here, the proposed technology integrates ultrathin epidural electronics into an electrocorticography array, therein simultaneously sampling brain signals in a large area for diagnostic purposes and delivering electrical pulses for treatment. The system is empirically tested to record the ictal‐like activities of the thalamocortical network in vitro and in vivo using the epidural electronics. Also, it is newly demonstrated that the electronics selectively diminish epileptiform activities, but not normal signal transduction, in live animals. It is proposed that this technology heralds a new generation of diagnostic and therapeutic brain–machine interfaces. Such an electronic system can be applicable for several brain diseases such as tinnitus, Parkinson's disease, Huntington's disease, depression, and schizophrenia. Abstract : Epidural electronic devices for multichannel recording of neuronal activities and delivering electrical pulses for treatment is developed using graphene electrodes. The system is empirically tested to record the ictal‐like activities of the thalamocortical network in vitro and in vivo.